The Candy Country - Alcott, Louisa May (Saga Egmont, 2022)
‘She also grew from a sickly, fretful child into a fine, strong woman.’From the author of ‘Little Women’, this short story follows the young girl Lily, who ends up in Candy country. Having taken her mother’s big red sun umbrella on a windy day, Lily is blown into a magical land made of sweets. Reminiscent of 'The Wizard of Oz', the story includes adventures surrounded by gingerbread, cakes, and cookies. But Lily eventually discovers that Candy country is not as sweet as it first seemed.Wholesome and filled with lessons applicable in our world today, ‘The Candy Country’ is one of Louisa May Alcott’s hidden gems.